Peranan Hukum Terhadap Konsumen Jual Beli Online di Indonesia - Wawan Fransisco (Ajudikasi : Jurnal Ilmu Hukum, 2019)
This scientific work is entitled the role of law on consumers of online buying and selling in Indonesia, in writing using normative legal research methods, namely by reading, studying, analyzing various laws and regulations, literature, scientific writings, and papers related to the material being examined. Online buying and selling is a way to shop through cyberspace or the internet where the payer uses a credit card or debit card, so without the need to meet face to face. Buyers or in this case consumers can order goods to sellers throughout Indonesia so easily. Therefore in this paper will explain in general about legal protection for consumers buying and selling online in Indonesian.